Slownik szkolny : zabytki kultury polskiej - Kaczorowski, Bartlomiej (Warszawa : Wydawnictwa Szkolne i Pedagogiczne, 1996)
A dictionary of Polish cultural monuments, buildings and churches, arranged for high school students. Ages 13-18.
Col. maps on lining papers.
One loose leaf inserted.
Includes index.
Keywords: Architecture -- Poland -- Dictionaries; Historic buildings -- Poland -- Dictionaries; Church architecture -- Poland -- Dictionaries